The Curse of the Excluded Middle. - MEIJER, ERIK (Communications of the ACM, 2014)
The article discusses the need for software developers to seriously consider embracing a pure lazy functional programming with all effects explicitly surfaced in the type system using monads. Topics discussed include a single global state as an unacceptable bottleneck in a parallel/concurrent/distributed world, a method that traces the return value of printf debugging style to the console, and a diagram that illustrates the Erlang version of the mutable Cell program through a tail-recursive function cell to hold the state of the Cell.